Spectral Analysis of the Term Structure of Interest Rates - Granger, C. W. J.; Rees, H. J. B. (Review of Economic Studies, 1968)
Journal Article Spectral Analysis of the Term Structure of Interest Rates Get access C. W. J. Granger, C. W. J. Granger University of Nottingham Search for other works by this author on: Oxford Academic Google Scholar H. J. B. Rees H. J. B. Rees University of Nottingham Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 35, Issue 1, January 1968, Pages 67–76, https://doi.org/10.2307/2974408 Published: 01 January 1968